From cave to dolmen : ritual and symbolic aspects in the prehistory between Sciacca, Sicily and the central Mediterranean - Gullì, Domenica (Archaeopress archaeology., 2014)
This text brings together the scientific contributions of a wide panel of Sicilian and mainland Italian specialists in prehistory. Taking inspiration from a conference organised by the Soprintendenza ai Beni Culturali e Ambientali of Agrigento and by the municipal council of Sciacca in November 2011, the decision was taken to broaden and deepen some of the main themes discussed on that occasion. Therefore this book focuses on the Sciacca region and its landscape which is extraordinarily rich in natural geological phenomena and associated archaeological activity, for example the Grotta del Kronio and the numerous dolmens present nearby.